Lanthanide complex-functionalized polyhedral oligomeric silsesquioxane with multicolor emission covered from 450 nm to 1700 nm. (30th October 2015) - Sun, Lining; Liu, Ying; Dang, Song; Wang, Zhuyi; Liu, Jinliang; Fu, Jifang; Shi, Liyi
Abstract : Six new hybrid materials covalently linking ternary lanthanide complexes to POSS were prepared, and the luminescent properties were investigated in detail. Abstract : A new 2, 2′-bipyridine-4, 4′-dicarboxylic acid-functionalized polyhedral oligomeric silsesquioxane (named as bpdc-POSS) was successfully synthesized. Subsequently, six new Ln-bpdc-POSS (Ln = Eu, Tb, Sm, Nd, Yb, Er) hybrid materials covalently linked with lanthanide complexes were prepared, based on the bpdc-POSS material acting as a matrix. The Ln-bpdc-POSS hybrid materials retain the structure of POSS and size distribution approximately 50 nm, and display visible as well as near-infrared luminescence (covered from 450 to 1700 nm wavelength region) under UV/visible light excitation. The Ln-bpdc-POSS materials (Ln = Eu, Tb, Sm, Er, Nd, Yb) were characterized by using wide-angle X-ray powder diffraction, Fourier-transform infrared (FT-IR) spectroscopy, high-resolution transmission electron microscopy (HRTEM), fluorescent spectroscopy and thermogravimetric analysis. The method offers advantages including the ease of synthesis and handling, as well as extending the use of POSS and expanding the field of luminescent inorganic–organic hybrid materials based on lanthanides.